STRATEGI PENGEMBANGAN AGROINDUSTRI DODOL SALAK DI DESA PANGU SATU KECAMATAN RATAHAN - Anisa ., Palit; Leonardus R. Rengkung; Eyverson ., Ruauw (AGRI-SOSIOEKONOMI, 2017)
This research aims to formulate internal and external strategy in developing Dodol Salak agroindustry in Pangu One Village. The study was conducted from March to May 2017 from preparation to the preparation of research reports. The data obtained in this research includes primary and secondary data. Primary data collection was done by interview technique to the respondent while secondary data was obtained by searching in the form of documents from related institution, seminar papers, This study used primary data and secondary data, with literature relevant to the research topic. The analysis used in this research is by using SWOT Analysis method. The results of this study indicate that the right strategy for the development of dolcol agroindustry in Pangu Satu Village, Ratahan Sub-district is to apply aggressive strategy, that is by creating creating process sorting of raw materials and better production equipment and utilizing manpower to produce superior product; through the process of sorting out the selection of good raw materials to increase revenue; companies use products that are free from preservatives and dyes to increase public interest in refined products; improve the process of sorting raw materials and the quality of health products to be more able to compete with existing companies; cooperate not only with one supplier (farmer); increase capital through related institutions such as Bank or other agencies; conducting human resource training to improve the company's work processes and increase opportunities for employers to create new jobs and reduce unemployment; increase capital income to prevent piracy of labor and utilize capital for infrastructure activities and transportation facilities.